Mutual Acceptance of Data (MAD) - Rao, K.S. (Biology, Engineering, Medicine and Science Reports)
In this short bulleting, I wish to bring to your attention an extremely important DEPARTURE of the agency to consider non-animal data as default which can sometimes be as important or even more. This is very historic in the umbrella of Mutual Acceptance of Data (MAD) that OECD will consider accepting non-animal data in support of safety, as a default.